2009
DOI: 10.1016/j.bbi.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in stimulated cytokine production following acute psychological stress

Abstract: Emerging evidence suggests that acute psychological stress modulates inflammatory competence; however, not all findings are consistent. Gender is one factor that may impact magnitude of response. To explore this possibility, we examined the effects of acute mental stress on lipopolysaccharideinduced production of pro-inflammatory cytokines interleukin (IL)-1 β, IL-6, and tumor necrosis factor (TNF)-α among a relatively healthy sample of midlife men (n=28) and women (n=34). Blood samples for the assessment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 53 publications
5
62
5
2
Order By: Relevance
“…Yet, the inflammatory responses observed in this study were of greater magnitude and were also sustained 75 min after stress exposure. This finding also adds support to a previous small study [16] that found sex differences in LPS-stimulated IL-6 production at 30 min post-stress between post-menopausal women compared to pre-menopausal women, and men. However, in that study, mental stress-related changes in unstimulated IL-6 levels were not observed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Yet, the inflammatory responses observed in this study were of greater magnitude and were also sustained 75 min after stress exposure. This finding also adds support to a previous small study [16] that found sex differences in LPS-stimulated IL-6 production at 30 min post-stress between post-menopausal women compared to pre-menopausal women, and men. However, in that study, mental stress-related changes in unstimulated IL-6 levels were not observed.…”
Section: Discussionsupporting
confidence: 88%
“…However, males had higher C-reactive protein (CRP) responses compared to females. Yet, another study in an older sample found no sex differences in stimulated IL-6 responses to a 5-min speech task 30 min post-stress [16]. However, in a subgroup analysis the authors observed that postmenopausal females had greater IL-6 responses compared to pre-menopausal females.…”
mentioning
confidence: 87%
“…[35][36][37][38] Interestingly, there were reports showing that significant differences in the levels of TNF-a production when females and males stimulated under certain physiological condition, such as psychological stress and early alcohol-induced liver injury. 39,40 In our study, the risk allele of rs1799724 (À857T) are known to have a significantly higher level of TNF-a production from concanavalin Aactivated peripheral blood mononuclear cells, 41 implying the importance of this variant in IA development, particularly in female IA.…”
Section: Discussionmentioning
confidence: 61%
“…For example, one study found that females showed greater IL-6 responses but smaller TNF-a to stress compared with males (Steptoe et al, 2002). Another study found that while there were no sex differences in the magnitude of the increase in cytokine production in response to social stress, there were sex differences in the recovery period (Prather et al, 2009).…”
Section: Discussionmentioning
confidence: 99%